(untitled) (Comprehensive Journal of Science, 2026)
This study aims to investigate the importance and benefits of mammography in the diagnosis of breast cancer through a field study conducted on patients attending the Oncology Hospital in Sabratha. The study adopted a descriptive approach, and a questionnaire was used as the main data collection tool. The results showed that the use of mammography is concentrated in the middle age groups (31–50 years), and it is considered one of the most effective methods for early detection of breast cancer. This contributes significantly to improving treatment outcomes and reducing complications. The study also revealed that the level of breast self-examination awareness is moderate and needs further improvement. The study recommends increasing health awareness, providing mammography devices in healthcare centers, and encouraging regular screening, as these measures play a vital role in reducing breast cancer incidence and mortality rates.